Filière forêt-bois et atténuation du changement - Roux, Alice; Colin, Antoine; Dhôte, Jean-François; Schmitt, Bertrand (éditions Quae, 2020)
While the main challenge in intertropical and boreal regions is tackling deforestation and forest resource degradation, forests and forestry in temperate regions face what may appear to be contradictory goals: to increase atmospheric carbon capture through sequestration in biomass and soils, while providing a growing share of the resources needed to produce essential material goods and energy for human societies as well as gradually renewing forests to enable them to adapt to future climate conditions. Creating a balance between these potentially competing priorities has been the subject of intense societal and scientific debate in recent years, which has prompted us to examine all aspects of these issues in greater depth. INRAE and IGN, at the request of the French Ministries responsible for agriculture and forestry, have jointly undertaken a scientific assessment to shed light on the details of this debate, using the example of forests and the forestry & wood sectors in metropolitan France. The results of this important exercise are presented in this book.